The Role of Sakinah Family Service Center (Pusaka Sakinah) to a Harmony Inside of Family During Pandemic Period on The Perspective of Maslahah Mursalah - Nabila, Farhanah Az Zahrowani (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
Pusaka Sakinah is a new program created by the Ministry of Religion to answer the problems of society related to marriage. The increasing problems caused by Covid-19 Pandemic indirectly affects the internal condition of harmony inside of family. The importance of assistance and counseling during pandemic is important to prevent conflicts in family. The Religious Affairs Office has a function to provide guidance services for sakinah families, so it can contribute greatly to solve the problems through Pusaka Sakinah. The objective of research was the description of Pusaka Sakinah’s implementation during pandemic in the Religious Affairs Office of Kedungkandang and the analysis of its role to harmony inside of family with the perspective of maslahah mursalah. This research is an empirical research with qualitative approach. The results of this study are: (1) The implementation of Pusaka Sakinah during pandemic is focused on solving cases of family disputes through one of the Pusaka Sakinah programs, namely the KOMPAK program; (2) The role of Pusaka Sakinah in the Religious Affairs Office of Kedungkandang is very important. Reviewed from the perspective of maslahah mursalah this program will provide great benefits for society in solving family problems that arise, especially during pandemic period.